School-wide social emotional learning (SEL) and bullying victimization: Moderating role of school climate in elementary, middle, and high schools - Yang, Chunyan; Chan, Mei-Ki; Ma, Ting-Lan (Journal of school psychology, 2020)
Guided by the school-wide social-emotional learning framework and social-ecological model, in this study we examined the associations between students' perceptions of four core social emotional learning (SEL) competencies (i.e., responsible decision-making, social awareness, self-management, and relationship skills) and school climate and their experience with bullying victimization through a multilevel framework. We also examined the multilevel moderating effects of students' perceptions of school climate, gender, and school levels (elementary, middle, and high schools) on the association between SEL competencies and bullying victimization. Participants were 23,532 students (4th to 12th grade) from 90 schools in Delaware. Using hierarchical linear modeling and controlling for demographic factors and school climate at both student and school levels, we found that three of the four core SEL competencies (i.e., social awareness, relationship skills, and self-management) and student-level school climate perceptions had significant associations with students' bullying victimization experiences. Moreover, the positive association between social awareness and bullying victimization and the negative association between self-management and bullying victimization were both mitigated in schools with more positive school climate at the student level. The association between some of the SEL competencies and bullying victimization varied depending on students' gender and grade levels. The findings highlight the unique and differentiated relations among the four core SEL competencies and students' bullying victimization experiences; they also suggest the importance of including school climate assessment and applying gender- and grade-level-specific efforts in bullying prevention programs with an SEL focus.